Ammu's Revolt Against the Caste System in Arundhati Roy'sThe God of Small Things (1997): A Feminist Approach - Nur 'Ainie, Nur 'Ainie, Dr. Phil.Dewi Candraningrum,M.Ed, Titis Setyabudi, S.S (2013)
The object of the research is a novel entitled The God of Small Things written by Arundhati Roy. The study focuses on the feminist perspective of the novel. The major problem of this study is to depict howAmmu revolts against the caste system reflected in Arundhati Roy's The God of Small Thing novel. The objectives of the study are to analyze the structural elements of the novel and to analyze the novel based on the feminist perspective. This research is the qualitative approach. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the novel itself. The method of the data collection is documentation research. The technique of data analyzes is descriptive analyzes. The results of the research show the following conclusions. Firstly, based on the structural analysis, Arundhati Roy wants to deliver a message to the reader that revolt against the caste system in The God of Small Things occurs because of social contexts. Secondly, based on the feminist analysis it shows that Arundhati Roy reflects the people reflected in the novel live under colonial rule and the caste system